Chilling the waste: Analysing household bread-freezing behaviours and their effect on bread waste - Jayanath Ananda; David Pearson; Sarah Hughes (Future Foods)
Consumer bread storage practices significantly affect the shelf life of bread, which is one of the most wasted food items in households. Addressing consumer bread waste is crucial for reducing overall food waste at home. However, despite the vital role of bread and bakery products in our diets, consumer behaviour regarding freezing bread has received limited attention. This research investigates the connection between bread-freezing habits and household bread waste based on a nationally representative sample of 2033 Australian households. Most households usually purchase white bread, followed by wholemeal bread. Approximately 27 % of respondents indicated that they freeze bread immediately after shopping, while most do not freeze or refrigerate it as the expiry date approaches. The likelihood of freezing bread rises significantly for those who buy larger quantities. Rural and isolated consumers are inclined to freeze bread right after shopping, while those not in the workforce are less inclined. The findings indicate that freezing bread at home effectively reduces bread waste.